Partial rupture of the distal biceps brachii tendon in elite waterpolo goalkeeper: a case report of conservative treatment - Giombini, A.; Innocenzi, L.; Di Cesare, A.; Di Salvo, W.; Fagnani, F.; Pigozzi, F. (The Journal of Sports Medicine and Physical Fitness, 2007)
The aim of this study was to describe a case of a 27-year-old male elite waterpolo goalkeeper, who had a partial rupture of the distal biceps tendon of his dominant arm while he was trying to save a strong outside shot. Pain on the antecubital fossa was the chief complaint. Ultrasound and magnetic resonance imaging completed the instrumental set-up. This case had the resolution of the pain and impairment after 3 months of conservative treatment. At 1-year follow-up, the athlete is asymptomatic and the isokinetic test provided almost complete recovery of the strength for elbow flexors and supinators muscles.